'When you heal the soil…': Environmental racism and socioecological repair in contemporary urban agriculture. Issue 4 (2nd October 2022) - Shostak, Sara
ABSTRACT: Drawing on data from an ethnographic study of urban agriculture in Massachusetts, this paper investigates the multiple meanings of soil for contemporary urban farmers and gardeners. I first consider how urban farmers speak for and with the soil in their neighborhoods to call attention to historical and ongoing environmental racism. These narratives highlight how racialized social processes – including redlining, blockbusting, white flight and disinvestment – have harmed the health of both people and the environment in urban communities of color. I then describe how urban farmers and gardeners articulate the importance of soil for health and well-being, especially for people whose relationships with the earth have been disrupted by capitalism, colonialism and racism. These narratives draw on both scientific and spiritual frameworks to highlight the healing potential of re-establishing direct relationships with nature, reclaiming ancestral knowledge about the healing properties of plants, and reconnecting with the ancestors themselves. Analysis of these interlinked narratives contributes to an emerging cross-disciplinary scholarship on the situatedness of ways of conceptualizing and interacting with soils, calling attention especially to the role of racialized inequities in the creation of harmful soil materialities and the possibilities of socioecological repair.